Synthesis, Characterisation And Molecular Docking Of Quinoxaline-isoxazole Hybrids As Potential Anti-hyperglycemic Agent - Phongphane, Lacksany (2024)
Diabetes mellitus is a chronic metabolic disorder that affects millions of people worldwide, leading to severe complications such as cardiovascular disease, obesity, and retinopathy. Despite advances in treatment, effective management of diabetes remains a significant challenge due to the limitations of current therapeutic options, including side effects and limited efficacy in controlling blood glucose levels. Hence, in our effort to develop anti-hyperglycemic agents that potentially inhibiting α-amylase and α-glucosidase enzymes, a series of new quinoxaline-isoxazole hybrids were successfully synthesised via five-step cyclisation. The new quinoxaline-isoxazole derivatives (84a-84v) were successful synthesised and obtained twenty-two compounds in a good yield within the range of 54% to 95%. Subsequently, these synthesised compounds were characterised and elucidated by several spectroscopies methods consisting of Fourier transform-infrared (FT-IR), and nuclear magnetic resonance (1D and 2D-NMR) including high-resolution mass spectrometry (HRMS). The synthesised compounds were further evaluated for the in vitro -amylase and -glucosidase inhibitory activities using acarbose as a positive control. Among 22 synthesised compounds, the results revealed that compound 84j showed dual inhibitory towards -amylase and -glucosidase with promising IC50 values of 17.0 and 40.1 μM, respectively. Moreover, compound 84c was also displayed the good dual activity for the inhibition of -amylase (IC50 = 24.0 μM) and -glucosidase (IC50 = 41.7 μM).